Higher education and the challenges of skills production in the Philippines - Adeyemo, Kolawole Samuel; Sehoole, Chika (South African Journal of Higher Education, 2016)
There has been a speedy increase in the number of higher education providers, including private higher education institutions in the Philippines. This proliferation of providers and institutional types has given rise to a need to address the issues of skills and relevance in the Philippines. The World Bank (2012) has reported on a significant gap between the skills needs of employers and the levels of skills produced by higher education institutions in the Philippines. How does the Philippines manage the increased demand for higher education to provide skills needed to develop the society and the economy? This article analyses the expansion of higher education globally and in the Philippines, in particular, and its impact on skills production. We argue the case for the proper regulation of the higher education system, in general, and private higher education, in particular, to deliver the relevant skills needed for the economic development and global competitiveness of the Philippines.